Feeling, healing, transforming, performing : unsettling emotions in critical transformative pedagogy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Williams, Meg Frances (Massey University, 2007)
This thesis takes a snapshot look at the experiences of five members of Te Rākau Hua o te Wao Tapu Trust, in order to illuminate the role of unsettling emotions in critical transformative pedagogy in Aotearoa New Zealand. An initial exploration of the literature reveals an historical gap in interest and research into the role of emotion in education, particularly the role of uncomfortable emotions. However, discomfort has increasingly become an interest of a number of critics who question the pedagogical emphasis on rational dialogue, believing it impotent to achieve the emancipatory aims of critical education. This thesis celebrates the unique contribution of Te Rākau to the healing and restoration of Māori communities and the transformation of the relationship between privileged and oppressed groups. Situated in a Kaupapa Māori methodological framework, the study positions the physical, emotional, and spiritual connectedness inherent to Māori worldviews as normal. A tension is therefore revealed between these norms and dominant Western norms, which are characterised by anti-emotional socialisation, compartmentalisation, and social fragmentation. This tension provides insights into the emerging interface between the fields of critical and transformative education, which stress the need to break down the Western dichotomies that separate human beings from nature, emotions from reason, and the personal from the political. The argument developed here suggests these dichotomies are seriously problematic for marginalised communities, who are not taken seriously until their circumstances reach acute crisis. These discussions reveal a pedagogy of healing, which is presented as crucial to the transformation of personal, social, economic, political, and ecological relationships, in which the contribution of uncomfortable emotions is invaluable. The heart of this work therefore urges us to embrace being unsettled in order to find the valuable messages and treasures discomfort reveals.
Keywords: Te Rākau Hua o te Wao Tapu Trust; Critical pedagogy; Transformative learning; Emotions; Maori (New Zealand people) -- Education; Whanaungatanga.; Kare-ā-roto.; Kura kaupapa Māori.; Mātauranga.; Tangata whenua.